Agricultural credits and agricultural productivity: Cross-country evidence - Unal Seven; Semih Tumen (Global Labor Organization (GLO), 2020)
We present cross-country evidence suggesting that agricultural credits have a positive impact on agricultural productivity. In particular, we find that doubling agricultural credits generates around 4-5 percent increase in agricultural productivity. We use two different agricultural production measures: (i) the agricultural component of GDP and (ii) agricultural labor productivity. Employing a combination of panel-data and instrumental- variable methods, we show that agricultural credits operate mostly on the agricultural component of GDP in developing countries and agricultural labor productivity in developed countries. This suggests that the nature of the relationship between agricultural finance and agricultural output changes along the development path. We conjecture that development of the agricultural finance system generates entry into the agricultural labor market, which pushes up the agricultural component of GDP and keeps down agricultural labor productivity in developing countries; while, in developed countries, it leads to labor-augmenting increase in agricultural production. We argue that replacement of the informal credit channel with formal and advanced agricultural credit markets along the development path is the main force driving the labor market response.
Keywords: J43; Q14; Q18; O47; 330; Agricultural credits; productivity; labor markets; financial development